Sulfasalazine-Induced Pancytopenia in Ulcerative Colitis (Journal of Enam Medical College, 2016)
Sulfasalazine is a well-established disease-modifying agent. It is commonly used in the treatment of rheumatic disorders and inflammatory bowel disease. The most frequently reported adverse effects are gastrointestinal effects, headache, dizziness and rash; myelosuppression can also occur. Patients treated with sulfasalazine can develop thrombocytopenia which is immune mediated. We report a case of ulcerative colitis that was on sulfasalazine subsequently developing thrombocytopenia.J Enam Med Col 2016; 6(3): 164-165